Penanaman Pendidikan Karakter di Lembaga Pendidikan Non-Formal (Studi Kasus di Homeschooling Group Khairu Ummah, Bantul) - Ichsan Wibowo Saputro (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
On the 21st century there are quite interesting changes in education, especially in Indonesia. It is showed by the emergence of home schools or commonly known as homeschooling. This is interesting enough to be observed considering the education model that previously existed in Indonesia. This model consists of three models involved pesantren, madrasah, and regular school. The concept of school is not only could be done in formal school but also in non formal schools, as well as informal. Moreover, some of the homeschooling that has emerged in recent years has identified itself as homeschooling that apply the concept of Islamic education. This research took Homeschooling Group (HSG) Khairu Ummah Bantul as the research object, mainly for character education. The transferring of Islamic characters in HSG Khairu Ummah Bantul uses the concept that begins with the process of education in the classroom. The next process uses exemplary method (uswah hasanah), advice (mau'izhah), habituation, reward and punishment. This processes allowed their knowledge changed into understanding (mafhum). Changes in basic concepts become the understanding is expected to form the mindset of Islam (aqliyah Islamiyah). Furthermore, understanding of morality is expected to metamorphose into a standard deed (miqyas) in the personal life of learners. If learners are able to continuously/ consistently shows attitude and speech according to morals, then can be called learners have been embedded nature of qona'ah. At this point in the learners have formed an attitude pattern of Islam (nafsiyah Islamiyah).